2019
DOI: 10.1111/wej.12476
|View full text |Cite
|
Sign up to set email alerts
|

Non‐steroidal anti‐inflammatory pharmaceutical wastewater treatment using a two‐chambered microbial fuel cell

Abstract: The two‐chambered microbial fuel cell (MFC) was designed and used for studying the efficiency of the real wastewater treatment from a non‐steroidal anti‐inflammatory pharmaceutical plant as well as from synthetic wastewater containing diclofenac sodium (DS). The removal of the contaminants was expressed regarding chemical oxygen demand (COD) removal, as measured by spectrophotometry experiments. Moreover, the effect of two different types of the cathode on current characteristics and COD removal was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…They also revealed that MFC reduced the phosphate concentration in the chemical industrial wastewater from 52.7 to 35.7 mg/L. Similarly, Amari et al, [33] reported that the 78 and 93% of COD of synthetic and pharmaceutical plant wastewater was reduced by dual-chamber constructed MFC (Plexiglas sheet). Furthermore, Ismail and his research group observed that Perspex glass made microbial fuel cell (MFC) with granular activated carbon (GSC) as biofilm successfully reduced up to 83% of pharmaceutical wastewater after continuous operation of 45 days [32].…”
Section: Cod and Tds Reductionmentioning
confidence: 86%
See 2 more Smart Citations
“…They also revealed that MFC reduced the phosphate concentration in the chemical industrial wastewater from 52.7 to 35.7 mg/L. Similarly, Amari et al, [33] reported that the 78 and 93% of COD of synthetic and pharmaceutical plant wastewater was reduced by dual-chamber constructed MFC (Plexiglas sheet). Furthermore, Ismail and his research group observed that Perspex glass made microbial fuel cell (MFC) with granular activated carbon (GSC) as biofilm successfully reduced up to 83% of pharmaceutical wastewater after continuous operation of 45 days [32].…”
Section: Cod and Tds Reductionmentioning
confidence: 86%
“…The 65 mL of wastewater (based on the available volume of the anode that was 70 mL) was taken into the anodic chamber along with 2 mL of the nutrient solution (the acetate solution) through the sampling opening on the lid of anode using the syringe. In the cathode chamber, 100 mM of the phosphate buffer solution having the neutral pH (pH 7) was added as the catholyte to increase the conductivity (M1000 Benchtop; Thomas Scientific, USA) and maintain the pH for electricity-generating bacteria [33].…”
Section: Mfc Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…MFC technology is capable of using organic waste as a substrate; consequently various types of waste both solid and liquid forms have been tested. These include a wide range of waste from common wastewater types such as domestic (Corbella and Puigagut 2018), dairy (Luo et al 2017), or food processing wastewater (Cecconet et al 2018) to "not-so-easy to clean" types of wastewater such as landfill leachate (Greenman et al 2009), mining wastewater (Ni et al 2016) and pharmaceutical wastewater (Amari and Boshrouyeh Ghandashtani 2019). Solid wastes such as municipal solid waste (Chiu et al 2016) and fruit and vegetable wastes have also been investigated (Venkata Mohan et al 2010).…”
Section: Bioelectrochemical Systems and Microbial Fuel Cellsmentioning
confidence: 99%
“…There are also reports on bioelectricity generation from (waste)water in MFCs by reducing heavy metals such as hexavalent chromium [10]. Hence, MFCs can be used efficiently to deal with industrial (waste)water contaminated by various organic and inorganic compounds such as pulp and paper [11], textile [12], and pharmaceutical [13] effluents.…”
Section: Introductionmentioning
confidence: 99%